(3GdNejS aj CMhGd CfaS GdfajSs - (3MSjf Hf eMeO Hf GdMSf GdOjGQ HcQj,J (B966 (3g` s ((3eMeO Hf eMeO GdOSjGhj s)
(3ChdgG (B:s
(3gPg eLehYI ai SjQ SjO GdeQSdjf hTeGFd NGJe GdfHjjf s
(3BNQgG (B:s
(3Ke Jhdi GdSdWfg HYOg GHfg GdSdWGf SdjeGf , hgh GdMGOi YTQ ef edhc Hfi YKeGf ai Chd GdbQf GdYGTQ s
(3GfXQ HQbe (B232 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B256 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B47s
Keywords: (3GdJGQjNs